Uwagi na temat „stanu odurzenia”, „środka odurzającego” oraz „środka działającego podobnie do alkoholu” w ujęciu przepisów karnych i prawa wykroczeń, w świetle ustawy z 29 lipca 2005 r. o przeciwdziałaniu narkomanii - Tkaczyk-Rymanowska, Katarzyna (PRAWO i WIĘŹ, 2021)
Broadly understood concept of „intoxication” can be found in many rules and regulations that use phrases that in fact introduce considerable terminological confusion. The Penal Code uses phrases: „intoxication”, „being under the influence of a stupefacient substance” or „other similarly acting agent” in various contexts. The author discusses what „intoxication” is and the concept of „intoxicant”. The authors also answer the question whether these terms include all psychoactive substances and which interpretation of the term „intoxicant” should be used for criminal liability of the perpetrator under the provisions of the Penal Code. The author also discusses the term „drug similar to alcohol” and how „a state of influence” and how a „state after use” a narcotic should be understood.